UTILIZATION OF HTML5-BASED INTERACTIVE MULTIMEDIA TO IMPROVE LEARNING IMPLEMENTATION SATISFACTION AND LEARNERS’ UNDERSTANDING IN E-LEARNING MANAJEMEN PEMBELAJARAN - Muh. Anang Al Aziz; Ridwan Sidik Kurniawan; Yudha Prapantja; Zulfitria Zulfitria (EDUPEDIA, 2026)
This study aims to analyze the utilization of HTML5-based interactive multimedia in the form of Sharable Content Object Reference Model (SCORM) on learning implementation satisfaction and learners’ understanding in the E-Learning Manajemen Pembelajaran at the Financial Education and Training Agency (BPPK). The research employed a descriptive qualitative approach supported by descriptive quantitative data. Data were collected through observations of the ongoing online learning implementation, participant satisfaction evaluations using a 1–5 Likert scale, and final quiz results as a summative test to measure learners’ understanding. The object of this study was HTML5-based interactive multimedia integrated into a Learning Management System (LMS) and accessed asynchronously by the training participants. The results indicate that participants’ satisfaction with the learning implementation was in the very good category, with perceived performance exceeding expectations. In terms of understanding, all participants were declared to have passed, as indicated by scores above the passing grade in the summative test. These findings suggest that the utilization of HTML5-based interactive multimedia packaged in SCORM format is able to provide a satisfying learning experience and effectively support learners’ understanding in e-learning, making it relevant for further development and implementation in online training programs within government institutions.